Study of Games Methodology Which Would Facilitate the Development of Expertise in The Use of Mixed Motive Games, Conflict Games and Players - Ritu Kumari; Dr. K. B. Singh (International Journal of Scientific Research in Science and Technology, 2025)
In this present paper, we study of the study of games methodology which would facilitate the development of expertise In the use of mixed motive games, Conflict games & players.
Keywords: Fuzzy Logic; Statistical Profiler; MATLAB